Integrative Human Biochemistry - Da Poian, Andrea T.; Castanho, Miguel A. R. B. (Springer, 2015)
Traditional lecture classes in biological sciences are being challenged by modern forms of communication. Modern communication tends to be more visual and less interpretative in nature. In lectures, the didactics are changing vastly and rapidly; the deductive power of mathematics is complemented by the intuitive clarity of movie simulations, even if the fi rst is fully embedded in the scientifi c method and the latter are mere artistic confi gurations of a faintly perceived reality. It is a general trend in modern societies that the most effective communication is more condensed and focused, contextualizes the information, and is disseminated across multiple media. Textbooks do not escape this reality. A modern scientifi c textbook to be effective should be a means of communication that needs to address specifi c issues of interest, place these issues in a broader interdisciplinary context, and make use of modern visualization tools that represent reality within the state of the art available in scientifi c research.
A Textbook for Medical Biochemistry
Keywords: Biochemistry